Analisa Tinjauan Klaim Reimbursement: Studi Kasus Kompensasi Finansial dalam Sistem Informasi Manajemen Keuangan - Bela Amalia Fernanda; Dewi Khrisna Sawitri (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
Amidst the digital transformation in human resource management, the provision of indirect financial compensation through health reimbursement schemes has become a strategic part in supporting employee welfare, especially in the public sector. Using a qualitative approach and a single case study design, data were collected through semi-structured interviews, direct observation, and document analysis. Research on the analysis of reimbursement claim reviews: a case study of financial compensation in a financial management information system shows that the high claim rejections in the Human Capital Division of an electricity company located in East Java were caused by ignorance of deadlines, unclear document requirements, damaged digital files, data input errors, and minimal socialization and technical training. The mismatch between the design of the digital system and the capabilities of users, especially retirees, indicates weaknesses in the implementation of the financial management information system. The results of the study on the analysis of reimbursement claim reviews: a case study of financial compensation in a financial management information system recommend more adaptive system updates and ongoing digital training to reduce technical rejections that are detrimental to users. Further studies are recommended to involve more work units and institutions to strengthen the generalization of the results and test the effectiveness of the solutions offered.